1996
DOI: 10.2105/ajph.86.6.804
|View full text |Cite
|
Sign up to set email alerts
|

Aiding troubled employees: the prevalence, cost, and characteristics of employee assistance programs in the United States.

Abstract: OBJECTIVES: Employee assistance programs (EAPs) are job-based programs designed to identify and assist troubled employees. This study determines the prevalence, cost, and characteristics of these programs in the United States by worksite size, industry, and census region. METHODS: A stratified national probability sample of more than 6400 private, nonagricultural US worksites with 50 or more full-time employees was contacted with a computer-assisted telephone interviewing protocol. More than 3200 worksites res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 8 publications
1
51
0
2
Order By: Relevance
“…Historically, Employee Assistance Programs (Chan et al, 2004;Employee Assistance Professional Association, 1990;Masi, 2005;Steele, 1989) were developed primarily to treat substance abuse among employees (Hartwell et al, 1996;Masi, 2002Masi, , 2005Moore and Forster, 1993). However, the scope of services has broadened beyond problem substance use to address all types of personal problems, including mental health and family issues (Masi, 2005;Roman, 1980;Steele, 1989) through assessment, brief intervention and counseling, referral services, employee orientation, employee outreach and education, and critical incident services (Masi, 2005).…”
Section: Employee Assistance Programs As a Model For College Student mentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, Employee Assistance Programs (Chan et al, 2004;Employee Assistance Professional Association, 1990;Masi, 2005;Steele, 1989) were developed primarily to treat substance abuse among employees (Hartwell et al, 1996;Masi, 2002Masi, , 2005Moore and Forster, 1993). However, the scope of services has broadened beyond problem substance use to address all types of personal problems, including mental health and family issues (Masi, 2005;Roman, 1980;Steele, 1989) through assessment, brief intervention and counseling, referral services, employee orientation, employee outreach and education, and critical incident services (Masi, 2005).…”
Section: Employee Assistance Programs As a Model For College Student mentioning
confidence: 99%
“…However, the scope of services has broadened beyond problem substance use to address all types of personal problems, including mental health and family issues (Masi, 2005;Roman, 1980;Steele, 1989) through assessment, brief intervention and counseling, referral services, employee orientation, employee outreach and education, and critical incident services (Masi, 2005). Despite the breadth of services provided within Employee Assistance Programs and their broad adoption by employers (Hartwell et al, 1996;Masi, 2005;Walsh et al, 1991), its effi cacy has not been well studied (Colantonio, 1989;Masi, 2005;Moore and Forster, 1993;Osilla et al, 2008). The limited research available has produced mixed support for the effi cacy of Employee Assistance Program services, in part because of the broad variety and variable quality of services delivered in these real-world settings (Chan et al, 2004;Osilla et al, 2008;Reynolds and Lehman, 2003;Walsh et al, 1991;Zarkin et al, 2001).…”
Section: Employee Assistance Programs As a Model For College Student mentioning
confidence: 99%
“…Accordingly, scholars and practitioners continue to share a deep interest in understanding how affective commitment to organizations develops. This pursuit is a foundational task for organizational scholarship (Mowday & Sutton, 1993).Searching for new ways to strengthen employees' affective commitment, many organizations have adopted employee support programs (Hartwell, Steele, French, Potter, Rodman, & Zarkin, 1996). Employee support programs are formalized practices designed to improve employees' experiences at work by providing emotional, financial, and instrumental assistance beyond the scope of standard HR pay, benefit, recognition, and training and development programs.…”
mentioning
confidence: 99%
“…Searching for new ways to strengthen employees' affective commitment, many organizations have adopted employee support programs (Hartwell, Steele, French, Potter, Rodman, & Zarkin, 1996). Employee support programs are formalized practices designed to improve employees' experiences at work by providing emotional, financial, and instrumental assistance beyond the scope of standard HR pay, benefit, recognition, and training and development programs.…”
mentioning
confidence: 99%
“…These programs now serve over 1/2 of the US workforce employed in companies with more than 50 workers (Hartwell et al, 1996b). Research has indicated that alcohol problems are reported as the presenting, contributing or related problem among approximately 1/3 of all clients served by EAPs (Blum et al, 1993).…”
Section: Discussionmentioning
confidence: 99%